An examination of block motion compensation algorithms for MPEG-2 and prediction of bit rates from video sequence measurements - Francis, Jerome Jonathan (Department of Electrical Engineering, 2016)
This dissertation examines the following two problems: • Finding a block motion compensation algorithm which is optimum in performance and speed. • Predicting the performance, for complex sequences, of an MPEG-2 encoder. An optimum motion compensation algorithm can lead to optimum temporal compression. For fixed bit-rate encoders finding methods to predict the bit-rate from properties of the video sequence can lead to an optimum use of the transmission bandwidth. The examination of motion compensation algorithms involved examining previous algorithms. Historically, one of three functions are used to evaluate a candidate motion vector, namely, Mean Square Error (MSE), Minimum Absolute Difference (MAD) and cross correlation. The ideal motion vector being the one that minimises MAD and MSE, and maximises cross-correlation. Sub-sampling, hierarchical and feature domain methods were examined. Finally some new algorithms are proposed and further areas of research suggested. The new algorithms suggested perform close to optimum, particularly those algorithms searching feature space.